Pengaruh Aset Tidak Berwujud, Kinerja Keuangan Dan GCG Terhadap Nilai Perusahaan (Studi Empiris Pada Perusahaan Manufaktur Sektor Consumer Non Cyclicals Yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2023) - Mira Cantika; Sri Anjarwati (Jurnal Ilmiah Raflesia Akuntansi, 2025)
Abstrak— This research aims to examine the influence of intangible assets, financial performance, and good corporate governance (GCG) proxied by independent commissioners on company value. The research employs a quantitative approach. The population consists of 127 consumer non-cyclical manufacturing companies listed on the Indonesia Stock Exchange from 2020 to 2023. A purposive sampling technique was utilized to select 80 companies. Data collection was conducted through documentation techniques, utilizing secondary data from financial statements and annual reports. The data analysis methods include regression analysis using EViews software. The results indicate that intangible assets have a significant effect on company value, financial performance significantly influences company value, and GCG, proxied by independent board commissioners, affects company value. This research is expected to provide deeper insights into the contributions of intangible assets, financial performance, and good corporate governance to the enhancement of company value. It is also hoped that this study will provide information for companies to leverage intangible assets and optimize GCG practices to create sustainable value.